1988
DOI: 10.1136/gut.29.3.306
|View full text |Cite
|
Sign up to set email alerts
|

Comparisons of the effects on satiety and eating behaviour of infusion of lipid into the different regions of the small intestine.

Abstract: SUMMARY Food intake and feelings of hunger and fullness were monitored in paired studies carried out in two groups of six healthy non-obese male volunteers during infusion of isotonic solutions of either a 50% corn oil emulsion or saline into the jejunum or into the ileum. Infusion of the lipid emulsion at a rate of 1-2 ml/min (4.9 kcal/min) into either the ileum or the jejunum significantly reduced the period of eating (p<0-01) and the quantity of food consumed (p<0O01), but neither affected the rates of drin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
81
1
2

Year Published

1996
1996
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 165 publications
(87 citation statements)
references
References 12 publications
3
81
1
2
Order By: Relevance
“…This results in delivery of calories to the ileum of 0.6 kcal min À1 and 1.8 kcal min À1 for the 3 and 9 g of oil in total, respectively, both being much lower than the 4.9 kcal min À1 in the studies by Welch et al 8,12 The 3 g ileal fat resulted in a reduction in appetite and an increase in satiety. This effect was comparable with that induced by the 9 g of ileal fat.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…This results in delivery of calories to the ileum of 0.6 kcal min À1 and 1.8 kcal min À1 for the 3 and 9 g of oil in total, respectively, both being much lower than the 4.9 kcal min À1 in the studies by Welch et al 8,12 The 3 g ileal fat resulted in a reduction in appetite and an increase in satiety. This effect was comparable with that induced by the 9 g of ileal fat.…”
Section: Discussionmentioning
confidence: 86%
“…22 A function of the ileal brake in the physiological regulation of gastrointestinal motility and secretion has been proposed. 23 The effect of lipids administered into the small intestine on satiety and food intake in humans has been studied previously by Welch et al 8,12 These authors demonstrated that infusion of fat in the ileum caused a reduction in food intake in healthy volunteers.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Although current research suggests that fat is the least satiating of the macronutrients (Rolls & Hammer, 1995), the issue remains unresolved (Welch et al, 1988;de Graaf et al, 1992;Blundell et al, 1996). It is possible that methodological differences between study designs may have contributed to this controversy (Rolls et al, 1988;de Graaf et al, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, different physicochemical properties of fats could influence their satiating properties. These include fatty acid chain length (Bach et al, 1996;Stubbs & Harbon, 1996;Van Wymelbeke et al, 1998), degree of fatty acid unsaturation (Shimomura et al, 1990;Lawton et al, 1997;Kamphuis et al, 2001), degree of emulsification (Welch et al, 1985(Welch et al, , 1988 and emulsion stability (Armand et al, 1992). In this context it has recently been shown that a fat emulsion (Olibra TM ) formulated from palm oil and oat oil fractions significantly decreased energy and macronutrient intakes in lean, overweight and obese subjects up to 36 h post-consumption (Burns et al, 2000(Burns et al, , 2001.…”
Section: Introductionmentioning
confidence: 99%